Abdurrauf Al-Singkili's Concept of Dhikr: Exploring the Sufi Psychotherapy Model - Ihsan, Nur Hadi; Sa’ari, Che Zarrina Binti; Kholid, Husna Hisaba (AL-TAHRIR, 2024)
The prevalence of mental health disorders in contemporary society underscores the need for effective psychotherapeutic approaches. While modern psychotherapy has made significant strides, the potential of Sufistic approaches, particularly in Islamic contexts, remains largely unexplored. This study examines the dhikr (remembrance of God) concept of Abdurrauf al-Singkili, a prominent 17th-century Indonesian Sufi, as a psychotherapeutic model. Through extensive library research, utilizing documentary techniques to analyze Abdurrauf's works and related scholarly materials, this study employs content analysis to elucidate his unique approach to dhikr. The findings reveal that Abdurrauf's dhikr concept offers a comprehensive Sufistic approach to psychotherapy, potentially serving as an alternative or complementary model in addressing current mental health challenges. Abdurrauf's conceptualization of dhikr as a means for spiritual fortification and psychological tranquility demonstrates remarkable parallels with contemporary meditation and relaxation therapy techniques. This research contributes to the growing body of literature on integrative psychotherapy, highlighting the relevance of traditional Sufistic practices in modern mental health interventions.